Experience of Brain Tumors in Tertiary Care Hospital - Akbar Shah, Asim Ishfaq, Muhammad Jalil Malik, Syed Muhammad Aun Ali Shah, Talha Bin Nasir, Syeda Rubab Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Brain tumors arising in the brain are called primary brain tumors. The brain tumors could be meninges, glands, nerves or brain tissue. Although brain tumors comprise of a small number of all cancers, but are disproportionately responsible for cancer-related deaths. The neoplasms may be low grade, high grade, primary tumor or metastatic. Aim: To evaluate the experience of brain tumors in a tertiary care hospital. Place and duration of study: Department of Neurosurgery, CMH, Lahore from March 2021 to March 2022. Methodology: This descriptive study included 38 patients. Age of patients ranged between 26 to 70 years and both genders having primary and secondary (metastatic) brain tumors who were considered fit for surgery were included. Patients who were unfit for anesthesia or unwilling for operation were excluded. Diagnosis of brain tumors was made by histopathology. Results: Mean age was 46.18±12.17 years. Male patients were 25(65.8%) and 13(34.2%) were female. All patients 38(100%) had headache 31(82%) patient had seizures, focal weakness in 26(68.42%) patients and 3(7.89%) patients had urinary/fecal incontinence. Majority of patients 16(42.11%) had glioblastoma, meningioma in 8(21.05%) patients while 3(7.89%) patients had pituitary adenoma. 15(39.47%) patients had tumor in right frontal lobe, 8(21.05%) patients in left parietal lobe and 4(10.52%) patients had tumor in right parietal lobe. Out of 3 patients, 1(2.63%) had right CP angle tumor, 1(2.63%) had in sphenoid ridge tumor, 1(2.63%) had tumor in Tuberculum Sallea respectively. Conclusion: It is concluded that male population had more brain tumor and glioblastomawas the most common tumor.